2010
DOI: 10.1007/s10681-010-0143-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of combining ability of two-types of male sterile and four restorer lines of Zinnia elegans

Abstract: Eight cross combinations of Zinnia elegans were made using two recessive nuclear male sterile lines crossed with four restorers using the North Carolina Design II statistical method. Heterosis, combining ability and heritability was analysed using 12 horticultural traits and these demonstrated the advantage of heterosis in hybrid breeding of Zinnia elegans. Heterosis served to increase the number of whorls of ray florets across capitulum and the number of branches, and also decreased plant height, crown size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…with the results obtained in other ornamental plants, such as gladiolus (Kumar et al 2008) and zinnia for plant height (Lou et al 2010). Our findings were also supported by the findings of Goksoy et al (2000) showing similar results for plant height in oil sunflower, while Ćirić et al (2013) suggested opposite results for plant height in oil sunflower.…”
Section: Resultssupporting
confidence: 91%
“…with the results obtained in other ornamental plants, such as gladiolus (Kumar et al 2008) and zinnia for plant height (Lou et al 2010). Our findings were also supported by the findings of Goksoy et al (2000) showing similar results for plant height in oil sunflower, while Ćirić et al (2013) suggested opposite results for plant height in oil sunflower.…”
Section: Resultssupporting
confidence: 91%
“…For other traits the magnitude of GCA variances was however higher than SCA variances which revealed preponderance of additive gene action for these traits (Tab. 2), which is in accordance with the results of Ahmad et al (2009) in tomato, Hemanthkumar et al (2008) in gladiolus, Hussein and Misiha (1978) in petunia and Lou et al (2010) in zinnia. Romanus et al (2008) and also Satija and Thukral (1985) have provided evidence for the greater importance of additive gene action in hybrid breeding outcomes.…”
Section: Resultssupporting
confidence: 87%
“…Estimates of specific combining ability (SCA) and reciprocal (RE) effects of hybrids for plant height at first flower, number of leaf to first flower, flower diameter, flower tube length, internode length and stem diameter in petunia 6.1 -9.9 ** *Significant at 5% level of probability; ** Significant at 1% level of probability 6). Similar results were obtained by Hussein and Misiha (1978) in petunia and Lou et al (2010) in zinnia. In case of flower tube length, hybrid P3 × P4 had the highest positive significant heterotic effects relative to the parental mean (16.2%) and high parent (11.7%) (Tab.…”
Section: Heterosis Relative To Mid (Mph) and High (Hph) Parentssupporting
confidence: 90%
“…When the plants entered the flowering stage, various morphological parameters, relating to the vegetative and flowering phenotypes of the mutant and control plants, were measured. The morphological parameters recorded were plant height (PH), crown size (CS), length of compound leaf (LCL), width of compound leaf (WCL), length of lobule leaf (LLL), width of lobule leaf (WLL), length of pedicel (LP), length of calyx (LC), height of flower bud (HB), width of flower bud (WB), diameter of inflorescence (DI), diameter of center disk (DC), number of florets (NF), and maximum number of flowers per day (MF) (Lou et al 2010). From each experiment replication, three plants were randomly selected and the data of 14 morphological parameters were recorded in October 2010.…”
Section: Morphological Observationsmentioning
confidence: 99%